Modelagem matemática : percepção e concepção de licenciandos e professores - Cozza, Fabio Espindola (2013)
This dissertation addresses the Modeling Mathematics in initial and continuing teaching education, presenting as its main purpose to analyze how different pedagogical interventions can modify the teachers‟ and students‟ perceptions about Modeling Mathematics. It takes, as its specific study, members of the Institutional Scholarship and Introduction to Teaching Program of the Mathematics Course from PUCRS - four supervising teachers and 19 undergraduate students. Supported by authors like Bassanezi and Biembengut, it shows how, historically, Mathematics Modeling becomes solid as a teaching and research method in Brazil. In studies developed by Biembengut, the author describes some pedagogical interventions that can serve as a theoretical and practical support for participants to develop and implement Modeling proposals in schools where they work. Methodologically, the research describes, categorizes, compares and analyzes data from a corpus of information from pre-and post-questionnaires, audio and video recordings taken during the meetings and written reports given at the end of each workshop.Through Discursive Textual Analysis, the research notes that most study subjects did not have contact with the mathematics modeling during their academic graduation, and, when they had the opportunity to know it, it was only about theoretical transmissions without going through its stages: interaction, mathematization and modeling. Initially, for these individuals, Modeling Mathematics is seen as a solution for problems in real life or a new teaching methodology. After the pedagogical interventions, the development and the implementation of the proposals, a significant change in these perceptions is evident, only four participants could not demonstrate an understanding of the concept of modeling as a method of research and teaching in the post questionnaire, although that group had succeeded during the implementation of the proposal. So, at the conclusion of this dissertation, among all the considerations mentioned, and after defending the modeling either as research method, the teaching method, the importance of training to break the disciplinary posture and the constitution of an expert stands out, since the problems presented in the student's reality do not refer to either a single subject or a specific area